2017
DOI: 10.1021/acssuschemeng.7b00641
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Pillared-Layer MOF as Efficient Visible-Light Photocatalysts for Aqueous Cr(VI) Reduction and Dye Degradation

Abstract: By using a controllable pillared-layer method, a novel visible-light responsive metal–organic framework (MOF) photocatalyst NNU-36 has been rationally constructed. The synthesized NNU-36 is of broad-range visible light absorption and good chemical stability which are beneficial to its application of photocatalysis. Photocatalytic experiments reveal that NNU-36 is highly efficient for Cr­(VI) reduction and dye degradation in aqueous solution under visible light irradiation. Control experiments show that the pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(121 citation statements)
references
References 54 publications
3
104
0
Order By: Relevance
“…As generally accepted, hydroxyl radicals (⋅OH) are the active species in the H 2 O 2 ‐involved photocatalytic reactions over MOFs . To verify the major active species in our system, tert ‐butyl alcohol (TBA) was used as a scavenger of hydroxyl radicals in the degradation reaction . As illustrated in Figure , the addition of TBA greatly depressed the photocatalytic efficiency for the degradation of RhB.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…As generally accepted, hydroxyl radicals (⋅OH) are the active species in the H 2 O 2 ‐involved photocatalytic reactions over MOFs . To verify the major active species in our system, tert ‐butyl alcohol (TBA) was used as a scavenger of hydroxyl radicals in the degradation reaction . As illustrated in Figure , the addition of TBA greatly depressed the photocatalytic efficiency for the degradation of RhB.…”
Section: Resultssupporting
confidence: 76%
“…[34] Xing's group recently reported that NNU-36 is ah ighly efficient heterogeneous photocatalystf or the reduction of aqueous Cr VI and degradation of dyes (rhodamine B: RhB;r hodamine 6G:R 6G, MLB). [35] These research reports, together with others, [36][37][38][39] have revealed the enormous potential held by MOFs for their use in photocatalytic removal of environmental contaminants.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The pillared‐layer approach is one of the few controllable ways to synthesize MOFs with fixed structural features, which typically relies on the introduction of bipyridine pillaring ligand combined with other carboxylate ligands to construct mixed‐linker MOFs with pillared‐layer structures. Studies have demonstrated that this method is highly feasible for the preparation of a series of isostructural MOFs with excellent physical and chemical stability . More importantly, it provides an easy way to realize desirable functionality of MOFs through conventional ligand modification.…”
Section: Introductionmentioning
confidence: 99%